If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -10) = 9x + -81 Reorder the terms: 8(-10 + x) = 9x + -81 (-10 * 8 + x * 8) = 9x + -81 (-80 + 8x) = 9x + -81 Reorder the terms: -80 + 8x = -81 + 9x Solving -80 + 8x = -81 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -80 + 8x + -9x = -81 + 9x + -9x Combine like terms: 8x + -9x = -1x -80 + -1x = -81 + 9x + -9x Combine like terms: 9x + -9x = 0 -80 + -1x = -81 + 0 -80 + -1x = -81 Add '80' to each side of the equation. -80 + 80 + -1x = -81 + 80 Combine like terms: -80 + 80 = 0 0 + -1x = -81 + 80 -1x = -81 + 80 Combine like terms: -81 + 80 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 3p-8+2p=22 | | 4w=w-12 | | 3p-8-2p=22 | | 9(x-9)=7x-81 | | x^2+x-72= | | 200=16-3x | | 70=10-4x | | 3c+9+5c=17 | | x^2+8x-33= | | 10-4x=9+2x | | 11u-4u-u=30 | | 5(x+6)=45 | | 48=10+2x | | 5x+6=45 | | x^2-11x+28= | | 75=9-7x | | 6p+3-4p+7= | | 7(x-8)=6x-54 | | -5x-4=36 | | 4x+6=38 | | x^2-6x-7= | | 3g+2g-5=20 | | x^2+3x+18= | | x^2+13x+40= | | 5x+3y=39 | | 3(n)+8=-23 | | x^2+3x+2= | | 5(1-2x)-3(4+4x)=0 | | 8x^7-x^8= | | 5x+3y=38 | | 38-4x=14 | | 8x-7=5(x-2) |